2021
DOI: 10.3390/app11041708
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Tele-Rehabilitation Program for Improving Upper Limb Function among Adults Following Elbow Fractures: A Pilot Study

Abstract: Active mobilization post-elbow fractures reduces the incidence of complications. Occupational therapists use tele-rehabilitation, incorporating technology into their practices. There is a lack of evidence-based trials regarding the integration of tele-rehabilitation during treatment. We therefore aimed to compare tele-rehabilitation treatment outcomes with conventional rehabilitation in improving the upper limb function post-elbow fractures. Methods: Eighteen participants post-elbow surgery due to fracture wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Although not designed to provide data to support tele-rehabilitation, TytoCare demonstrates the ability of a small, inexpensive medical device to support healthcare providers in the diagnosis and treatment of common ailments (e.g., ear infections, sore throats, fever, allergies, pink eye, nausea, respiratory infections, and common skin conditions) [ 40 ]. Meditouch’s ArmTutor and 3D Tutor systems provide feedback of elbow range of motion to treat upper limb function post-elbow fractures via a tele-rehabilitation protocol similar to conventional rehabilitation [ 41 ]. The hardware includes wireless electro-optical sensors which detect and display joint movement.…”
Section: Discussionmentioning
confidence: 99%
“…Although not designed to provide data to support tele-rehabilitation, TytoCare demonstrates the ability of a small, inexpensive medical device to support healthcare providers in the diagnosis and treatment of common ailments (e.g., ear infections, sore throats, fever, allergies, pink eye, nausea, respiratory infections, and common skin conditions) [ 40 ]. Meditouch’s ArmTutor and 3D Tutor systems provide feedback of elbow range of motion to treat upper limb function post-elbow fractures via a tele-rehabilitation protocol similar to conventional rehabilitation [ 41 ]. The hardware includes wireless electro-optical sensors which detect and display joint movement.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, more and more other studies discussed the implications of telemedicine in orthopedics from various aspects. [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Remote rehabilitation has been used by some occupational therapists. The performance of the upper elbow (when comparing remote rehabilitation and traditional rehabilitation) was evaluated for elbow fracture improvement [25]. Results showed that the satisfaction reported with remote rehabilitation was much higher.…”
Section: Introductionmentioning
confidence: 99%